From pathogenic mechanisms to therapeutic perspectives: a review of gut microbiota and intestinal mucosal immunity in inflammatory bowel disease - Han, Tianqi; Zhang, Yiwen; Zheng, Gang; Guo, Yi (Frontiers in Immunology, 2025)
Inflammatory bowel diseases (IBDs), which comprises Crohn’s disease (CD) and ulcerative colitis (UC), is a multifactorial disorder with an as-yet undetermined etiology, with its global incidence rising rapidly, particularly in developing and Western countries. Although the exact etiology remains unclear, recent research implicates genetic predisposition, environmental factors, gut microbiota, and immune responses in the pathogenesis of IBD. Notably, dysbiosis of the gut microbiota—characterized by a reduction in the abundance and diversity of specific bacterial genera—has been suggested as a potential trigger for the onset of IBD, accompanying with dysregulated intestinal mucosal immunity involving in immune cells and nonimmune cells. Understanding and restoring the imbalanced gut microbiota, as well as identifying key bacterial species involved in IBD, are critical for elucidating disease mechanisms and developing therapeutic strategies. In this review, we explore the role of gut microbiota and intestinal mucosal immunity in the pathogenesis of IBD and offers insights into microbiota-centered therapeutic interventions, including probiotics, fecal microbiota transplantation, and microbial metabolites, that aim to modulate the gut microbiota for the treatment of IBD.